2018
DOI: 10.24815/siele.v5i2.9697
|View full text |Cite
|
Sign up to set email alerts
|

Boosting students’ speaking ability through Community Language Learning

Abstract: This study was done to find out the effect of using the Community Language Learning (CLL) Method for teaching-learning speaking English with second semester students in the English Education Study Program at a private university in West Java in an effort to improve the English speaking skills of the students. This study used an action research method where the researcher was accompanied by an observer as a collaborator. Three cycles were done for this study. Data were gathered from observations, a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Based on the English curriculum for junior high school in Indonesia, students are required to master the speaking skill and they should get a score above the minimum passing grade, which is about 70-80, depending on each school's policy. However, until today, speaking is still being one of the students' difficulties in learning English for many learners, especially in Indonesia (Fitriani & Zulkarnain, 2019;Halimah, 2018;Hanifa, 2018). Bada, et al (2011) said that speaking is one of the difficult English skills to improve because the students have limited time to recall words and to care for pronunciation, intonation, and responses, which interrupts the speech, and causes additional difficulties for the speaker.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the English curriculum for junior high school in Indonesia, students are required to master the speaking skill and they should get a score above the minimum passing grade, which is about 70-80, depending on each school's policy. However, until today, speaking is still being one of the students' difficulties in learning English for many learners, especially in Indonesia (Fitriani & Zulkarnain, 2019;Halimah, 2018;Hanifa, 2018). Bada, et al (2011) said that speaking is one of the difficult English skills to improve because the students have limited time to recall words and to care for pronunciation, intonation, and responses, which interrupts the speech, and causes additional difficulties for the speaker.…”
Section: Introductionmentioning
confidence: 99%
“…Teaching speaking skill is more challenging than other language skills in the EFL (English as a Foreign Language) context (Halimah, 2018;Usman et al, 2018), such as the case with Indonesian students. So teachers should prepare the best strategy which suits well to the context they are teaching in.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That key idea is also reflected in EC and ECC. Thus, previous studies of this research take English corner (EC) from Kellaway (2013) and Cantero & Sanderson (2018), English Conversation Club (ECC) from Kurniasih (2019), and Community Language Learning (CLL) from Halimah (2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, EC in this current research engages the facilitator to guide, facilitate, and manage the activity. Third, a finding from Halimah (2018) entitled Boosting students' speaking ability through Community Language Learning. Halimah's finding showed that Community Language Learning (CLL) can boost students' speaking ability.…”
Section: Introductionmentioning
confidence: 99%